2021
DOI: 10.1038/s41598-021-86746-6
|View full text |Cite
|
Sign up to set email alerts
|

New insights into microstructure of neutron-irradiated tungsten

Abstract: The development of appropriate materials for fusion reactors that can sustain high neutron fluence at elevated temperatures remains a great challenge. Tungsten is one of the promising candidate materials for plasma-facing components of future fusion reactors, due to several favorable properties as for example a high melting point, a high sputtering resistivity, and a low coefficient of thermal expansion. The microstructural details of a tungsten sample with a 1.25 dpa (displacements per atom) damage dose after… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 60 publications
0
16
1
Order By: Relevance
“…A detailed understanding of the interaction of W with the fusion products (helium and neutron) and the fusion fuel (deuterium (D) and tritium) is needed, especially because tritium is a scarce and radioactive element. Tungsten exposure to fusion products generate morphology changes in the bulk of W, as numerous studies have shown [1][2][3][4], and the influence of such bulk defects onto fusion fuel retention is presently an active field of research [5,6]. In contrast, pure surface effects are often neglected in plasmawall interaction studies and global recycling coefficients are used for simulating edge plasma physics [7].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed understanding of the interaction of W with the fusion products (helium and neutron) and the fusion fuel (deuterium (D) and tritium) is needed, especially because tritium is a scarce and radioactive element. Tungsten exposure to fusion products generate morphology changes in the bulk of W, as numerous studies have shown [1][2][3][4], and the influence of such bulk defects onto fusion fuel retention is presently an active field of research [5,6]. In contrast, pure surface effects are often neglected in plasmawall interaction studies and global recycling coefficients are used for simulating edge plasma physics [7].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, He peak may appear shifted towards the W plasmon in the overpressurized bubbles [39,61,58]. Lastly, a presence of impurities such as oxygen in the substrate (e.g., oxidation) or inside the bubble may add another contributions to the spectrum [53].…”
Section: Density and Gas Pressure In Helium Bubblesmentioning
confidence: 99%
“…Over the past decades, extensive microstructural characterizations of W alloys have already been carried out to understand the microstructural response to neutron irradiation [7,[9][10][11][12]. It can be concluded that neutron irradiation can cause the formation of lattice defects such as dislocation loops, Frenkel pairs and vacancies in the W alloys [13,14], and Materials 2022, 15,1985 2 of 14 can also lead to the formation of rhenium-(Re)-or osmium-(Os)-rich precipitates due to the trigger transmutation process [15,16]. However, owing to low irradiation intensity, long experimental periods, radioactive problems and resource shortages, researchers mostly used different kinds of heavy ion irradiation to screen tungsten materials because of the more obvious damage effect as well as the flexible control for experiment parameters [17,18].…”
Section: Introductionmentioning
confidence: 99%